Origin of friable sediments of the Barents Sea shelf. - Krapivner, R B (PANGAEA, 2009)
The origin of friable sediments blanketing the Barents Sea shelf is considered. It is shown that their characteristic seismoacoustic record patterns reflect low degree of diagenetic transformations and indicates continuous sedimentation. According to traditional views, this single sedimentary complex also includes diamicton, and the section is interpreted as a three-unit structure: diamicton, which is considered a till; the overlying friable sediments accumulated under different conditions of deglaciation in glaciomarine settings; and the postglacial marine sediments. It is demonstrated that such views are inconsistent with geomorphologic features (datings by physical methods included) indicating a prolonged hiatus that separates epochs of the diamicton accumulation and formation of friable sediments. The analysis revealed that the composition, vertical succession, and lateral distribution of different lithological types of friable sediments are related to the regular spatiotemporal replacements of different facies settings in the transgressing Arctic sea rather than by the glacial process. This inference is confirmed by the composition of foraminiferal assemblages.
14C ages, grain size distribution and foraminifer abundance of sediments from the Barents Sea shelf
Keywords: Archive of Ocean Data; ARCOD